2016
DOI: 10.1055/s-0036-1586393
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical bone turnover markers in children and adolescents

Abstract: Bone is a dynamic tissue that consistently undergoes remodeling. During formation and resorption processes, bone turnover markers are released. They are specific bone-derived molecules that circulate in the blood or are present in the urine reflecting the bone metabolic activity (during childhood and adolescence: bone growth in length, modeling and remodeling). The use of biochemical bone turnover markers provides dynamic indices of bone turnover and complements the static measures of bone, such as measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Rising levels of estrogen and other sex hormones are accompanied by the secretion of growth hormone and insulin‐like growth factor I, which stimulates greater bone turnover during puberty compared to other phases of life. (Pater and Nowacki, 2012). However, the bone turnover response to vitamin D supplementation suggests an overlap between the age groups we examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rising levels of estrogen and other sex hormones are accompanied by the secretion of growth hormone and insulin‐like growth factor I, which stimulates greater bone turnover during puberty compared to other phases of life. (Pater and Nowacki, 2012). However, the bone turnover response to vitamin D supplementation suggests an overlap between the age groups we examined.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no age-specific reference data are available for serum markers of bone turnover in basketball players. In this sense, it has been suggested that the increase in bone turnover markers coincides with the pubertal growth spurt (Pater and Nowacki, 2012). The rapid process of bone modeling and remodeling with progression through puberty could potentially increase the need for vitamin D in this accretive phase of life (Stagi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%